First report of Hirnantian (Upper Ordovician) high-latitude peri-gondwanan macrofossil assemblages from Portugal. (26th December 2018) - Colmenar, Jorge; Pereira, Sofia; Young, Timothy P.; da Silva, Carlos M.; Sá, Artur A.
Abstract: The first report of the Hirnantia high-latitude peri-Gondwanan Fauna from Portugal (Upper Ordovician, Ribeira do Braçal Formation) is presented here. The described macroassemblages are fairly diverse containing fossils of brachiopods, trilobites, echinoderms, machaeridians, and ostracodes. Among the brachiopods, the most abundant is Mirorthis mira . Plectothyrella cf. P . libyca, Paromalomena cf. P . polonica, Plectoglossa ? sp., and a small indeterminate discinoid are also present. The trilobites are represented by abundant sclerites of Mucronaspis cf. M . mucronata, and an isolated cranidium and pygidium assigned to Flexicalymene . The occurrence of Mucronaspis and Flexicalymene represents the first record of these genera in Portugal. Echinoderms are dominant in the basal bed of the formation; the columnal plates tentatively ascribed to morphogenus Pentagonocyclicus are the most abundant, followed by the echinosphaeritids. Abundant disarticulated machaeridian plates, of the genus Plumulites, associated with trilobites are present in one of the localities. Ostracodes were found in one single locality and have been assigned tentatively to the genus Herrigia . Ramose and massive bryozoans also occur in the assemblage. This new macrofossil assemblage supports the assignment of an Hirnantian age for the Ribeira do Braçal Formation. Most of the brachiopod species and the dalmanitid Mucronaspis are commonly present in Hirnantian deposits globally, but the presence in the assemblage of a brachiopod close to Plectothyrella libyca, a cold-water species, previously reported only from the Hirnantian of Libya and Morocco, is noticeable. This strengthens the case for a high latitudinal setting of the present-day territory of the Portuguese Central Iberian Zone during the Late Ordovician.